Association of birth order with adolescent mental health and suicide attempts: a population-based longitudinal study. - Easey, Kayleigh E.; Mars, Becky; Pearson, Rebecca; Heron, Jon; Gunnell, David (European Child & Adolescent Psychiatry, 2019)
Previous cohort studies have observed higher birth order to be associated with increased risk of suicidal behaviour. However, the mechanisms underlying this association are unclear. Using data from the Avon Longitudinal Study of Parents and Children (ALSPAC), we used multivariable logistic regression models and mediation analysis to investigate the associations of birth order with adolescent suicide attempts and psychiatric disorder. We investigated whether the number of maternal depressive episodes and father absence mediated the associations found. In fully adjusted models (n = 2571), higher birth order was associated with an increased risk of both suicide attempts (OR = 1.42, CI = 1.10–1.84) and psychiatric disorder (OR = 1.29, CI = 0.99–1.69). Maternal depression and father absence only partially mediated (8%; 12%) these associations. Whilst maternal depression and paternal absence partially mediated the associations between birth order, and suicidal behaviour and psychiatric disorder, other pathways may account for much of these associations. Future studies should investigate alternative mediating pathways.